On the asymptotic properties of continuous solutions of the systems of nonlinear functional equations - Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
For systems of nonlinear functional equations, we study asymptotic properties of their solutions continuously differentiable and bounded for t ≥ T > 0 in a neighborhood of the singular point t = +∞.